Seeds for an Encounter Ethics: The Fruit of Reading Veritatis Splendor Beyond a Post-Conciliar Binary Narrative - Catherine Moon (Journal of Moral Theology)
Two of the more recent methodological narratives about twentieth-century moral theology, written by James Keenan and Matthew Levering, argue that an intractable methodological division over law and conscience emerges in the wake of Vatican II. Within these narratives, _Veritatis Splendor_ is situated as authoritatively taking sides amidst this division, leaving _Veritatis Splendor_’s key methodological insights out of view. While (re)turning to a more spiritual approach to moral theology, the Second Vatican Council does not set out a clear method for the discipline but instead leaves post-conciliar moral theology with the task of figuring out how to do moral theology according to this new paradigm. _Veritatis Splendor_ ought to be read as a continuation and deepening of this post-conciliar moral methodological project set in motion by Vatican II. Through the concept of “encounter with Christ” and its emphasis on the lives of the saints, _Veritatis Splendor_ plants seeds for the development of a post-conciliar moral theological method consistent with the methodological task set out by the Second Vatican Council, a foundational point of methodological continuity between “revisionists” and “traditionalists,” and responsive to unresolved methodological concerns from the Council.